2018
DOI: 10.3390/app8081254
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of GLONASS Inter-Frequency Code Biases in Precise Point Positioning (PPP) International Time Transfer

Abstract: Abstract:International time transfer based on Global Navigation Satellite System (GLONASS) precise point positioning (PPP) is influenced by inter-frequency code biases (IFCBs) because of the application of frequency division multiple access technique. This work seeks to gain insight into the influence of GLONASS IFCBs on international time transfer based on GLONASS-only PPP. With a re-parameterization process, three IFCB handling schemes are proposed: neglecting IFCBs, estimating IFCB for each GLONASS frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…where r indicates the receiver, S indicates the satellite; P S r,IF and L S r,IF denote the pseudo-range and the phase observables in metres, respectively; λ S IF is the carrier wavelength when ionosphere-free; Φ S r,IF is the original carrier phase measurement in cycles; ρ is the geometric distance in metres; c denotes the speed of light; dt S and dt r are the clock offsets of the satellite and receiver in seconds; e is the elevation angle of the satellite S; m f w (e) refers to wet mapping functions [19]; Z w represents the zenith wet delay; d S r,IF and d S IF are the uncalibrated code delays (UCDs) of the IF model at the receiver and satellite end, respectively; N S r,IF is an integer itself but is estimated as a floating point number from unmodeled effects; b S r,IF and b S IF are the uncalibrated phase delays (UPDs) of the IF model at the receiver and the satellite ends in cycles; and ε S r,IF and ξ S r,IF denote the sum of the measurement noise and the multipath error for the pseudo range and carrier phase observations, respectively. Since d S IF is absorbed by the satellite clock [20], the clock offset of the receiver dt r can be written as follows [8]:…”
Section: The Observation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where r indicates the receiver, S indicates the satellite; P S r,IF and L S r,IF denote the pseudo-range and the phase observables in metres, respectively; λ S IF is the carrier wavelength when ionosphere-free; Φ S r,IF is the original carrier phase measurement in cycles; ρ is the geometric distance in metres; c denotes the speed of light; dt S and dt r are the clock offsets of the satellite and receiver in seconds; e is the elevation angle of the satellite S; m f w (e) refers to wet mapping functions [19]; Z w represents the zenith wet delay; d S r,IF and d S IF are the uncalibrated code delays (UCDs) of the IF model at the receiver and satellite end, respectively; N S r,IF is an integer itself but is estimated as a floating point number from unmodeled effects; b S r,IF and b S IF are the uncalibrated phase delays (UPDs) of the IF model at the receiver and the satellite ends in cycles; and ε S r,IF and ξ S r,IF denote the sum of the measurement noise and the multipath error for the pseudo range and carrier phase observations, respectively. Since d S IF is absorbed by the satellite clock [20], the clock offset of the receiver dt r can be written as follows [8]:…”
Section: The Observation Modelmentioning
confidence: 99%
“…Second, our approach does not produce jumps that may accelerate clock offset convergence. The Allan deviation (ADEV) is employed to obtain the frequency stability [8,28], which is also utilized to further assess the performance of RT-PPP solutions, using five kinds of precise products. In this contribution, Stable32 software (http://www.wriley.com/) is applied to calculate ADEV.…”
Section: Appl Sci 2019 9 X For Peer Reviewmentioning
confidence: 99%
“…The results showed that the accuracy and stability of the uncombined model can be identical to the conventional ionosphere-free (IF) model [13]. Ge et al investigated the contribution of inter-frequency bias (IFB) on time transfer based on GLONASS-only PPP and demonstrated that estimating IFB for each GLONASS satellite was better than estimating IFB for each frequency number [14]. Dach et al analyzed the influence of inter-frequency and intersystem bias on time transfer with GPS and GLONASS [15].…”
Section: Measurement Science and Technologymentioning
confidence: 99%
“…By the development of multi-GNSS, PPP with multi-GNSS observation has achieved a hot topic for time comparison. Ge, et al [25] presented GLONASS PPP time transfer with inter-frequency code biases (IFCBs) model. BDS PPP using triple-frequency observation was investigated by Tu, Zhang, Zhang, Liu and Lu [21].…”
Section: Introductionmentioning
confidence: 99%